O FUNDEB como política pública de financiamento da educação básica e seu desempenho ao longo dos anos nos municípios mineiros - Bernardo, Rosangela Ferreira (2017)
This study analyzes the FUNDEB in the State of Minas Gerais, seeking to understand what factors lead a given municipality to gain or lose resources with FUNDEB and, from this observation, to verify the consequences in terms of allocation of resources destined to early childhood education and elementary education. The data show that the amount sent by the municipalities for FUNDEB formation is influenced by economic and financial factors. On the other hand, the values received from FUNDEB are influenced by population factors such as enrollment in elementary education and the resident population. The data also reveal that in the State of Minas Gerais in the analyzed period 52.87% of the municipalities lose resources with FUNDEB. Regarding the allocation of resources, it was found that in municipalities that lose resources, investments in early childhood education are lower, with primary education being given priority, these municipalities also invest more than 93% of the resources received in the valuation of teaching professionals and 30.4 % Of its revenues in the maintenance and development of education. In municipalities earning funds from FUNDEB, investments are uniform in both types of education; Apply about 81.24% of the resources received from FUNDEB and about 30% of their revenues from taxes and transfers in the maintenance and development of education.